2005
DOI: 10.1210/me.2005-0015
|View full text |Cite
|
Sign up to set email alerts
|

A Peroxisome Proliferator-Activated Receptor α/γ Dual Agonist with a Unique in Vitro Profile and Potent Glucose and Lipid Effects in Rodent Models of Type 2 Diabetes and Dyslipidemia

Abstract: LSN862 is a novel peroxisome proliferator-activated receptor (PPAR)alpha/gamma dual agonist with a unique in vitro profile that shows improvements on glucose and lipid levels in rodent models of type 2 diabetes and dyslipidemia. Data from in vitro binding, cotransfection, and cofactor recruitment assays characterize LSN862 as a high-affinity PPARgamma partial agonist with relatively less but significant PPARalpha agonist activity. Using these same assays, rosiglitazone was characterized as a high-affinity PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 58 publications
1
44
0
4
Order By: Relevance
“…It was recently reported that a PPAR␣/␥ agonist elevated pyruvate dehydrogenase kinase isozyme 4 (PDK4) mRNA levels in liver compared with vehicle or a PPAR␥ agonist (42). In the present study, we checked PDK4 mRNA levels in liver and epididymal adipose tissue and found that PDK4 mRNA levels in epididymal adipose tissue of Wy-14,643-treated KKAy mice were significantly higher than those of vehicle-treated KKAy mice (data not shown), indicating that PPAR␣ was actually activated in adipose tissue by Wy-14,643 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that a PPAR␣/␥ agonist elevated pyruvate dehydrogenase kinase isozyme 4 (PDK4) mRNA levels in liver compared with vehicle or a PPAR␥ agonist (42). In the present study, we checked PDK4 mRNA levels in liver and epididymal adipose tissue and found that PDK4 mRNA levels in epididymal adipose tissue of Wy-14,643-treated KKAy mice were significantly higher than those of vehicle-treated KKAy mice (data not shown), indicating that PPAR␣ was actually activated in adipose tissue by Wy-14,643 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…16,17) In recent years, several structurally diverse PPAR dual agonists or PPAR pan agonists have been discovered. [17][18][19][20][21][22] Although several of them have been discontinued because of various side effects such as carcinogenesis in preclinical murine models, the effects of some new class of dual and pan PPAR agonists on the regulation of glucose and lipid metabolism with improved safety patterns have been demonstrated in experimental animal models.…”
Section: Discussionmentioning
confidence: 99%
“…20,21) Hence novel PPARa/g dual agonists are promising agents to combat metabolic disease with better profile. 17) In addition, partial PPAR agonists with modest response such as metaglidasen are developed in many companies including Metabolex, Roche, Evolva, and Astellas, with the goal of retaining beneficial effects of this class of agents while diminishing their adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that a PPAR-γ partial agonist similar to LSN862, i.e. (S)-2 methoxy-3-{4-[5-(4-phenoxy)pent--1-ynyl]phenyl}-propionic acid, has better antidiabetic activity and weaker side effects than the TZDs [98]. More recently, a novel family of PPAR-γ partial agonists (pyrazol-5-yl benzenesulfonamide derivatives) with either high potency or specificity in vitro or glucose-lowering efficacy in vivo has been identified [75].…”
Section: B Cmentioning
confidence: 99%